Integration of Islamic and Positive Law: Sociological Review of PMA No. 38/2017 - Nor Mohammad Abdoeh; Anandi, Rizki Parahita; Saputra, Heru (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The phenomenon of the emergence of PMA No. 38 Year 2017, makes a big challenge for the academic community of the Faculty of Shari'ah UIN Salatiga in order to realize the quality of alumni who not only master the science of Islamic Law, but also master general law. This study examines the impact of the implementation of PMA No. 38/2017 on the curriculum and teaching methods at the Faculty of Shari'ah UIN Salatiga, and how this harmonization affects the social and academic dynamics within the faculty. Using a sociological approach, this study assesses how the curriculum changes affect the relationship between lecturers, students and educational institutions, and the implications for the quality and relevance of legal education in Indonesia. The findings show that despite significant efforts to harmonize the two disciplines, fundamental differences in methodologies and perspectives remain a major obstacle. The research also reveals the social impact of this integration on students, lecturers, and the academic community as a whole, and offers recommendations to improve the effectiveness and acceptability of scholarly harmonization in the future. The efforts made by the Faculty of Shari'ah in harmonizing science are to conduct a curriculum review by involving alumni and stakeholders. The impact of the change in degree after the issuance of PMA No. 38 of 2017 is the acceptance of alumni of the Islamic Family Law Study Program at the Faculty of Sharia UIN Salatiga with the initials FS in the M.Kn Master of Notarial Program at Sebelas Maret University Surakarta, this is proof that sharia graduates are eligible to become notary. This is because a number of degrees in the field of sharia studies related to law (such as Islamic Family Law (Ahwal Syakhshiyya), Sharia Economic Law and Constitutional Law (Siyasah Shar'iyyah) have now been uniformed with a law degree. This is as illustrated in the attachment of PMA 33/2016 and its amendments.